2016
DOI: 10.1080/00423114.2016.1158411
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of driver actions in RWD race car including tyre thermodynamics

Abstract: The paper presents an innovative method for a lap time minimisation by using genetic algorithms for a multi objective optimisation of a race driver-vehicle model. The decision variables consist of 16 parameters responsible for actions of a professional driver (e.g. time traces for brake, accelerator and steering wheel) on a race track part with RH corner. Purpose-built, high fidelity, multibody vehicle model (called 'miMa') is described by 30 generalised coordinates and 440 parameters, crucial in motorsport. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…It is shown that there is value in the current rubber theory but considerable scope for further research on the mechanics of rubber friction exists. The sixth paper, written by Maniowski [6], closes the special issue by highlighting the importance of tyres in relation to vehicle handling. The author explores the influence of temperature-sensitive tyre characteristics on vehicle behaviour and driving strategy by solving the multi-parametric optimisation problem of the minimum lap time at a race circuit.…”
Section: Special Issue On the 4th International Tyre Colloquiummentioning
confidence: 96%
“…It is shown that there is value in the current rubber theory but considerable scope for further research on the mechanics of rubber friction exists. The sixth paper, written by Maniowski [6], closes the special issue by highlighting the importance of tyres in relation to vehicle handling. The author explores the influence of temperature-sensitive tyre characteristics on vehicle behaviour and driving strategy by solving the multi-parametric optimisation problem of the minimum lap time at a race circuit.…”
Section: Special Issue On the 4th International Tyre Colloquiummentioning
confidence: 96%
“…Much of the literature on tyre thermal modelling is related to the accuracy provided in the simulations in model-based development of vehicles [17][18][19][20][21][22]. These models range from simple empirical-lumped models to high-fidelity finite element method(FEM)-based physical models.…”
Section: Tyre Thermal Modellingmentioning
confidence: 99%
“…Thus, to avoid the issue an of algebraic loop, the load transfer (∆F z ) was modelled as first-order dynamics [27], as a function of the tyre longitudinal force, as shown in ( 17) and (18). Thus, the load transfer was a state in the full-car dynamics, eventually increasing the DOF from 9 to 10, as seen in (20).…”
Section: -Dof Vehicle Prediction Modelmentioning
confidence: 99%
“…From the modelling point of view, the research effort has been therefore addressed to the modelling and estimation of all those quantities not directly acquirable even with the state of art sensing technology, but which could represent a key factor in the continuous improvement of control algorithms and logics to be employed in the increasing expansion of interconnected and smart vehicles [4][5][6][7][8]. Different approaches for modelling the tyre thermomechanical behaviour can be found in literature [9][10][11][12][13] as well as various practical case studies [3,[14][15][16], which testify the attention payed to the topic.…”
Section: Introductionmentioning
confidence: 99%